PEMBENTUKAN KONSEP DIRI ORANG DENGAN HIV/AIDS (ODHA) DI KOTA PEKANBARU DALAM PERSPEKTIF FENOMENOLOGI - Pius Ady Sinaga; Welly Wirman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The problem faced by people with HIV / AIDS (ODHA) is not just a problem of decreasing physical condition but also social issues such as acceptance of negative labels and forms of discrimination from the social environment. Received the negative label ODHA affected how people living with HIV against him or himself. Self concept is the decisive factor in interpersonal communication, because everyone behaves in accordance with the concept itself. The purpose of this research was to determine how self-concept construck people with HIV / AIDS (ODHA) in Pekanbaru.This study was conducted from January to June 2015 at the Sebaya Lancang Kuning foundation Pekanbaru. This study used a qualitative research method with data collection techniques of observation, interviews, documentation. The object of this study is the concept of self-people living with HIV in the city of Pekanbaru with a phenomenological perspective. The number of informants in this study were as many as six people consisting of one founder of the foundation, 2 people patient of HIV / AIDS one other people who work in health and two people closest to people with HIV / AIDS. Subject retrieval using snow ball sampling technique. For data analysis techniques using the Miles and Huberman. To check the validity of the data, researchers used data triangulation techniqueThe results showed that the self-concept of ODHA in Pekanbaru city as a whole are at unfavorable category. This finding is supported by the fact that many people with HIV / AIDS really want to try to improve their behavior but their negative attitude of society to change the concept of people living with HIV themselves into a negative direction. Due to the worse is the cause of understanding themselves as individuals who are unwanted and may become a useful person who function normally in society makes people living with HIV have a negative self viewKeywords : ODHA, HIV/ AIDS, Social Patology